Pathophysiological significance of measuring exhaled gasotransmitters during exercise - Yoshifumi Yasuda (Japanese Society of Physical Fitness and Sports Medicine, 2013)
The gaseous signaling molecules, nitric oxide (NO), carbon monoxide (CO) and hydrogen sulfide (H2S) have been identified as being produced endogenously in a variety of cells, and are also found to be involved in diverse and pivotal pathophysiological roles including neurotransmission, cellular metabolism, immunological/inflammatory responses, and various aspects of cardiovascular regulation in the human body. These gases can diffuse freely through a membrane and exert their own roles when binding with a variety of molecular targets in a cell. These gaseous molecules can also be detected in the exhaled air, and can change their volume in the presence of diseases and/or exercise. However, the real origin and pathophysiological implications of these gases in the exhaled air are largely uncertain. This review attempts to summarize the generation and biological roles of NO, CO and H2S, and to advert the pathophysiological significance of measuring these gases in exhaled air with respect to exercise and exercise training.